Control of using robust H∞ control with genetic algorithm - Kalamullah, Mohammed; Faris, Waleed Fekry; Hasbullah, Faried; Ghazaly, Nouby M. (Science and Engineering Research Support Society, 2019)
Better ride comfort and controllability of vehicles are pursued by automotive industries by considering the use of suspension system which plays a very important role in handling and ride comfort characteristics. Comprehensive comparison on half car model was conducted to analyze the effect of active suspension system, using Robust H-infinity on the model. Passive suspension system is also compared with active suspension technique for the purpose of benchmarking. Parametric uncertainties are used to model the non-linearities associated in the system. Genetic Algorithm is used to develop weighting function for robust control design purpose. Comparison of all models also shows that in spite of adding uncertainties in the system, the designed Robust H-infinity controller achieved better settling time than the traditional passive suspension system. © 2019 SERSC.